Ativismo judicial na perspectiva comparada entre o direito e a ciência política: remédio ou veneno para a democracia? - Oliveira, Marcos Rogério Félix de (2019)
The term “judicial activism” has been widely used in the media, well as in the academic papers. It turns out, however, that this is an ambiguous term. Thus, the present work initially sought to find the origins of this expression and to analyze the discourse in which it was used, with the intention of extracting the original meaning of what Judicial Activism would be. It was noticed throughout the study that the author of this expression, Arthur M. Schlesinger Jr., did not intend to create a concept, which turned out to be an effect produced. Despite not intending to create a concept, through the narrative of his text we were able to establish the elements that would characterize Judicial Activism, proposing our concept of Judicial Activism and Self-Containment. From this definition, we proceeded to the study of Judicialization of Politics, with the historical rescue of the expansion of the Judiciary Power, which led, in our opinion, the emergence of this phenomenon. Thus, from the study of the relevant literature, it was possible to extract the various meanings in which this term is used and, based on all these elements, we formulate a concept of Judicialization of Politics, in order to differentiate it from Judicial Activism. Then, we started to study the Politicization of the Judiciary, establishing the various meanings in which this expression can be used, also in order to differentiate them from the other terms. Once the conceptual question was solved, the path through which the studies of Judicial Activism for Law and Political Science went through was established, establishing, in the end, the different trajectories and conceptions of this term for each of the sciences. Finally, the question was answered as to whether Judicial Activism is the poison or the remedy for Democracy.